Campos de batalha da cidadania no Norte de Moçambique - Marina Padrão Temudo (Cadernos de Estudos Africanos)
For many years, the idea that the civil war ravaging Mozambique was led by a mercenary army at the service of external interests was unquestioned. It was not known that Renamo had a social basis of rural support and that agricultural production constituted a funding source for the war. After Independence, the Frelimo Party-State provoked a social, economic, political and cultural destructuring of rural societies, leading an authoritarian and centralized project of development and nation-building that jeopardised fundamental rights of citizenship. The joining the war of part of the population could thus be seen as an attempt to conquer these rights.Through two contrasting case studies, in this paper I intend to unveil the strategies of social and economic reproduction that made it possible for populations to survive during the conflict and to recreate their livelihoods in the aftermath, as well as the multilayered ways the affirmation of citizenship rights can take on.